Isolated unilateral orbital myeloid sarcoma: a case report - Sonalika, Chintakunta; Sneha, Latha M.; Jayaraman, Dhaarani; Backiavathy, Varsha; Subramanian, Krishnakumar; S., Sri Gayathri; John, Christopher (International Journal of Contemporary Pediatrics, 2022)
Myeloid sarcoma (MS) is a rare solid tumor consisting of immature myeloid cells occurring at an extramedullary site. It can present before, with, or after the manifestation of acute myeloid leukemia or other myeloproliferative diseases, and a few patients never develop bone marrow infiltration. Only a few isolated cases of pediatric orbital MS have been reported, and they are often misdiagnosed. We report a rare case of pediatric isolated orbital MS in a 5-year-old boy who presented with unilateral proptosis. The patient was diagnosed with MS based on MRI and Immunohistochemistry results. Subsequently the patient underwent chemotherapy supported with radiotherapy and showed significant response. Isolated orbital MS presents with clinical and radiological features which are often misleading, making the diagnosis difficult. Therefore, MS should be considered in the differential diagnosis of orbital masses and proptosis even in the absence of acute myeloid leukemia (AML).